Effectiveness of the Village Apparatus Empowerment Program in Village Financial Management in Mandailing Natal Regency - Brutu, Anjur; Ritonga, Syafruddin; Jamaluddin, Yanhar (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to analyze the effectiveness of the village apparatus empowerment program in village financial management in Mandailing Natal Regency. This empowerment program is designed to increase the capacity of village officials in managing and supervising the allocation of village funds to be more transparent and accountable. The method used in this study is a qualitative approach with case studies. Data collection was carried out through in-depth interviews, participatory observations, and documentation involving village officials, program assistants, and village communities. Data analysis was carried out using thematic analysis techniques. The results show that the effectiveness of the empowerment program is influenced by four main indicators, namely communication, resources, disposition, and organizational structure. Effective communication between the district government, assistants, and village officials supports the understanding of village financial management. However, there are obstacles in delivering information to the public. Limited human resources and technology are obstacles in the implementation of the program, especially in remote areas. The positive disposition of most village officials in applying the principles of transparency and accountability has had a positive impact, although there is resistance to change among more senior village officials. A clear organizational structure and good coordination between village officials have been proven to increase the effectiveness of village financial management. The conclusion of this study is that the success of the village apparatus empowerment program in village financial management is highly dependent on the synergy between communication factors, resources, disposition, and organizational structure.